Natural Resistance in Teak to Spodoptera litura (Fabricius) Boursin (Lepidoptera: Noctuidae) - Roychoudhruy, N.; Joshi, K. C. (Indian Forester, 2000)
Nine selected phD tree progenies of Teak, (Tectona Grandis L.f.) belonging to Orissa (ORANR-2, ORANR-3, ORANR-4, ORANP-7 and ORPB-15), Andhra Pradesh (APT-8 and APT-14), Tamil Nadu (TNT-2) and Maharashtra (MHSC-AS) were evaluated for their natural variation in resistance to Spodoptera litura, a major pest of Teak in nursery stage. On the basis of percentage incidence and average damage intensity, plus tree progeny of ORANR-3 and APT-14 were observed to be most resistance and most susceptible respectively. Feeding observationS revealed that larvae prefer mature leaves of Teak, irrespective of plus tree progeny.